Development of Augmented Reality Learning Media Using a Deep Learning Pedagogical Approach to Improve Early Childhood Scientific Literacy - Nida'un Nabila; Yaswinda Yaswinda; Nenny Mahyuddin; Nurhafizah Nurhafizah (MASI Mandiri Edukasi, 2026)
Scientific literacy is a fundamental competency that should be developed from early childhood, yet many early childhood education institutions continue to rely on conventional instructional media that offer limited opportunities for interactive, meaningful science learning. Although Augmented Reality (AR) has demonstrated potential for enhancing learning engagement, few studies have integrated AR with a deep learning approach to foster early childhood scientific literacy through meaningful, mindful, and joyful learning experiences. Therefore, this study aimed to develop and evaluate Augmented Reality learning media based on a deep learning approach to improve children's scientific literacy at RA Al Qur’an Dina. This Research and Development (R&D) study employed the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. Data were collected through interviews, observations, expert validation questionnaires, response questionnaires, and pretest–posttest instruments involving early childhood learners. The findings indicated that the developed media were valid and feasible, as assessed by media, material, and instrument experts. The results of the Focus Group Discussion (FGD), small group trials, and Training of Trainers (TOT) also confirmed that the media were practical, engaging, and easy to implement. Furthermore, large-group testing demonstrated a substantial improvement in children's scientific literacy, reflected in an N-Gain score of 0.98 (high category) and an effectiveness level of 97.93% (highly effective category). In conclusion, the developed Augmented Reality learning media effectively enhanced early childhood scientific literacy through interactive and meaningful learning experiences.